Fruit and vegetable biotechnology - Valpuesta, Victoriano (Woodhead Publishing in food science and technology., 2002)
The genetic modification of foods is one of the most significant developments in food processing, and one of the most controversial. This important collection reviews its application to fruit and vegetables. Part 1 looks at techniques and their applications in improving production and product quality. Part 2 discusses how genetic modification has been applied to specific crops, whilst Part 3 considers safety and consumer issues.